Symposium 3: Bridging Networked Learning between the Knowledge Economy and Higher Education: A Philosophical Approach - Parchoma, Gale; Dykes, Mary (Proceedings of the International Conference on Networked Learning, 2008)
McLuhan (1964) predicted that the future of work would involve learning a living. Information technology would merge production, consumption and learning into an automated process. This process of automation would result in a global learning society. A growing body of evidence suggests that McLuhan's prediction of the emergence of a global learning society has been realized and its knowledge economy (KE) has become a catalyst forcing complex socioeconomic and educational issues to the fore in public and private organizations and in higher education. The KE has a constant, even insatiable need for a well-educated, continuously learning, and networked workforce, which can efficiently produce information, knowledge, and innovation. The rapid pace of change in the KE quickly depreciates knowledge workers' expertise which must continuously be updated with structured formal and informal education and training offered at educational institutions or through professional programs, and unstructured informal education and training, such as life skills learned at home, work, and in the community. This process of continuous learning, training and re-training, is called lifelong learning. Knowledge workers' lifelong learning needs have resulted in an emergent category of higher education learners, who typically need to simultaneously balance career and family commitments with formal participation in higher education. Universities have responded to the needs of this group through introducing a variety of non-traditional delivery modes, including networked learning (NL). NL has been heralded as a technological innovation, capable of transforming learning and globalizing higher education, and has been critiqued as a commercial venture into mass commodification and impoverishment of higher learning. In this paper, we argue that the process involved in learning in both the knowledge economy and in higher education can be reclaimed as a human process that uses technology as a tool, rather than a process that is driven by the technology itself. We focus on the process of connections that occur in NL via using information technology to link learners, tutors, and learning resources. We propose that NL can be developed and facilitated with an ethic of care for learners in both the KE and higher education within the traditions of academic culture and values through judicious structural, cultural, economic, and pedagogic adaptations within institutions of higher education. Drawing on the literature of learner-centred instructional design, networked learning, networked learning communities, and ecological learning environments, we reclaim pedagogical discourses from their misuse in the "cyberlibertarian rhetoric of mass commodification" (Greener & Perriton, 2005) associated with globalization of NL in higher education. We posit a philosophy of democratic approaches to NL pedagogy, which may bridge knowledge workers' learning experiences in higher education to critical, reflective participation in distributed communities of practice within the knowledge economy.